2020
DOI: 10.1038/s41598-020-64128-8
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput, Label-Free Quantitative Proteomic Studies of the Anticancer Effects of Electrical Pulses with Turmeric Silver Nanoparticles: an in vitro Model Study

Abstract: Triple negative breast cancer (TNBC) represents 15-20% of the over one million new breast cancer cases occurring each year. TNBC is an aggressive cancer phenotype, with low 5-year survival rates, high 3-year recurrence rates, and increased risk of metastasis. A lack of three commonly exploited hormone receptors renders tnBc resistant to endocrine therapies and lends to its critical absence of viable therapeutic targets. This necessitates the development of alternate and effective novel therapeutic strategies f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 65 publications
(86 reference statements)
0
9
0
Order By: Relevance
“…129,130 A recent study demonstrated the anticancer effects of ECT against the MDA-MB-231 cell line, which is representative of the TNBC subtype. 131 These effects include the suppression of key proteins involved in the proliferation, differentiation, migration, survival, and apoptosis of cancer cells.…”
Section: Immunotherapymentioning
confidence: 99%
“…129,130 A recent study demonstrated the anticancer effects of ECT against the MDA-MB-231 cell line, which is representative of the TNBC subtype. 131 These effects include the suppression of key proteins involved in the proliferation, differentiation, migration, survival, and apoptosis of cancer cells.…”
Section: Immunotherapymentioning
confidence: 99%
“…G3BP (also known as 90‐kDa Mac‐2‐binding protein), which was before unreported associated with TNBC, is a member of the beta‐galactoside‐binding protein family. Additionally, another study also identified ENO1 as a potential biomarker of TNBC 100 …”
Section: Proteomic Analysis Of Tnbcmentioning
confidence: 97%
“…Such permeabilization is characterized by the uptake of external nonpermeant molecules in the cell cytoplasm and leakage of internal substances from the electropermeabilized cells [ 4 , 5 , 6 ]. Since then, this technique has being used and developed in several areas of biotechnology and medical research, such as bacterial transformation [ 7 , 8 ], cell electrofusion [ 9 , 10 ] transdermal drug delivery [ 11 , 12 ], CRISPR editing [ 13 ], CAR-T cell generation [ 14 ], DNA vaccines, including for the novel Sars-CoV-2 coronavirus [ 15 , 16 , 17 ], gene therapy [ 18 , 19 , 20 , 21 ], cancer treatment [ 22 , 23 , 24 ] and even in food processing [ 25 , 26 ] and environmental sanitation [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%